Gen-Y men and 'Fast Fashion': Who values it?. Issue 1 (1st September 2019) - Sung, Jihyun; Woo, Hongjoo
Fast fashion refers to the clothing that follows the latest fashion trends at affordable prices. Although fast fashion could cause environmental, social and ethical issues, it has been widely consumed by young consumers because of its various styles with inexpensive prices. Thus, the current study investigated how Gen-Y males' varied decision-making styles influence their perceptions towards fast fashion differently. The results of an online survey collected from 335 Gen-Y males showed that there are two different decision-making groups: indifferent realists and conscious fashionistas, which were dissimilar in their ethnic distribution. Further, their varied decision-making dimensions influenced their perceptions towards fast fashion differently. These results contribute towards the existing literature related to fast fashion and provide insightful perceptions for fast fashion marketers in targeting Gen-Y male consumers.